Pengaruh Model Pembelajaran Talking Stick Terhadap Hasil Belajar pada Mata Pelajaran IPA Kelas IV SD Negeri 5 Rambang - Atma, Adiya; Imansyah, Farizal; Marleni, Marleni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Good learning outcomes are something that is aspired to from the learning process, but not allstudents get good learning outcomes as expected. The purpose of this study was to determine the effect of the talking stick learning model on learning outcomes in science subjects at SD Negeri 5 Rambang. The method used in this study is a quantitative (experimental) method in the form of a non-equivalent control group design. The population of this study were all fourth graders of SD Negeri 5 Rambang. The sample used in this study is class IV B as the experimental class totaling 33 students and class IV A as the control class totaling 33 students. Data collection techniques used in this study are test and documentation techniques. The data analysis technique was carried out using the-test. Based on the test results, the students' average score for the experimental class after using the talking stick learning model was 67.45 and the average test score of the control class students was 60.71. This shows that the talking stick learning model can affect student learning outcomes.